2011
DOI: 10.1002/joc.3409
|View full text |Cite
|
Sign up to set email alerts
|

Moisture transport into the Ethiopian highlands

Abstract: ABSTRACT:The Ethiopian summer rains occur as air masses of various origins converge above the Ethiopian plateau. In this study, the relative importance of different moisture transport branches has been estimated using the Lagrangian trajectory model FLEXPART, and ERA-Interim reanalysis data, to backtrack air reaching the northern Ethiopian highlands in July-August 1998-2008. The Indian Ocean, the Congo Basin and the Red Sea were found to be important moisture source regions; for air from the Indian Ocean aided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(120 citation statements)
references
References 45 publications
3
116
1
Order By: Relevance
“…The transport in April was similar to the transport in the driest spring seasons discussed by , whereas easterly anomalies in the July-August transport above Central Africa are known to cause reductions in the inflow of moisture to the Ethiopian highlands (Segele, Lamb et al 2009;Williams, Funk et al 2011;Viste and Sorteberg 2011;Viste and Sorteberg 2012). The question remains whether these -or other relevant atmospheric anomalies -were connected, or whether the dry spring in 2009 being followed by a dry summer, was just an unfortunate, random combination.…”
Section: Atmospheric Moisture Transport In 2009mentioning
confidence: 55%
See 1 more Smart Citation
“…The transport in April was similar to the transport in the driest spring seasons discussed by , whereas easterly anomalies in the July-August transport above Central Africa are known to cause reductions in the inflow of moisture to the Ethiopian highlands (Segele, Lamb et al 2009;Williams, Funk et al 2011;Viste and Sorteberg 2011;Viste and Sorteberg 2012). The question remains whether these -or other relevant atmospheric anomalies -were connected, or whether the dry spring in 2009 being followed by a dry summer, was just an unfortunate, random combination.…”
Section: Atmospheric Moisture Transport In 2009mentioning
confidence: 55%
“…During the northern hemisphere summer, air masses from the Indian Ocean, Central Africa and the Red Sea region flow toward Ethiopia (Mohamed, Hurk et al 2005;Korecha and Barnston 2007;Levin et al 2009;Segele, Lamb et al 2009;Viste and Sorteberg 2011). As shown in Figure 9b, this causes strong moisture convergence above the Ethiopian highlands.…”
Section: Atmospheric Moisture Transport In 2009mentioning
confidence: 97%
“…Mohamed et al (2005) indicated that the moisture flux for the northern Ethiopian plateau has mainly Atlantic origin. However, a recent moisture transport study by Viste and Sorteberg (2013) in the Ethiopian highlands reported that the moisture flow from the Gulf of Guinea, the Indian Ocean and from the Mediterranean region across the Red Sea and the Arabian Peninsula are identified as the main sources of moisture transport in the region. According to their study, the largest contribution to the moisture transport into the northern Ethiopian highland was attributed to the air travelling from the Indian Ocean and from the Mediterranean region across the Red Sea and the Arabian Peninsula.…”
Section: Potential Moisture Source Areas For the Study Areamentioning
confidence: 99%
“…Rainfall in Ethiopia shows large variations across time and space, due to the complex topography and varying latitude of the country (Gamachu 1988). Temporally, it varies from days to decades, with the magnitude and direction of historic rainfall trends varying from region to region and season to season (Seleshi and Zanke 2004;Cheung et al 2008;Jury and Funk 2012;Viste and Sorteberg 2013). Spatially, the amount, seasonal cycle, onset and cessation times of rainfall as well as the length of growing season, are all variable across the country (Gamachu 1988;Segele and Lamb 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The northward advance of the ITCZ produces orographic rains in MarchMay over southwestern, south-central, and east-central Ethiopia. Low pressure over South Sudan draws in a moist flow from the Indian Ocean and Gulf of Aden (Segele et al 2009a;Viste and Sorteberg 2013), producing the main rains in southern and southeastern Ethiopia and the secondary rain for the eastern, east-central and northeastern parts of Ethiopia (Seleshi and Zanke 2004). Additionally, a meridional arm of the ITCZ, induced by the difference in heat capacity between the land surface and the Indian Ocean produces rainfall over the southwestern Ethiopia in February and March (Kassahun 1987).…”
Section: Introductionmentioning
confidence: 99%